Analisis komparatif Pembiayaan Pendidikan dan Prestasi Akademik di Madrasah dan Sekolah Negeri Kota Samarinda: Comparative Analysis of Education Financing and Academic Achievement in Madrasahs and Public Schools in Samarinda City - Rinda Cahya Mudiawati; Syawal Arifin; Siti Djulaikah; Widyatmike Gede Mulawarman (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study analyses the link between education funding and student achievement at State Madrasahs and State Schools in Samarinda City. It also examines the roles of teacher quality, school facilities, and student development programs. Using a quantitative comparative correlation method, the study sampled 241 eleventh-grade students: 129 from State Madrasahs and 112 from State Schools, chosen through proportionate stratified random sampling. Data collection included a Likert scale questionnaire, academic records, and interviews with teachers and the treasurer. Descriptive statistics, Pearson's correlation, multiple regression, and the Independent Samples T-Test were used for analysis. Findings showed high to very high levels for education funding, teacher quality, school facilities, and development programs. Pearson's test revealed a strong positive relationship between funding and achievement: r = 0.65 for State Madrasahs and r = 0.68 for State Schools (p < 0.05). The four variables together explained 67% of the variation in achievement. The t-test confirmed significant institutional differences. Public schools used funds more for facilities, while public madrasas focused on teacher competency and religious guidance. Education funding has a significant impact on academic achievement, with effectiveness shaped by each institution's management and characteristics.